Slope of Kidney Function and Its Association with Longitudinal Mortality and Cardiovascular Disease among Individuals with CKD - Orlandi, Paula F. (J Am Soc Nephrol, 2020)
BACKGROUND: Slopes of eGFR have been associated with increased risks of death and cardiovascular events in a U-shaped fashion. Poor outcomes in individuals with rising eGFR are potentially attributable to sarcopenia, hemodilution, and other indicators of clinical deterioration. METHODS: To investigate the association between eGFR slopes and risks of death or cardiovascular events, accounting for multiple confounders, we studied 2738 individuals with moderate to severe CKD participating in the multicenter Chronic Renal Insufficiency Cohort (CRIC) Study. We used linear, mixed-effects models to estimate slopes with up to four annual eGFR assessments, and Cox proportional hazards models to investigate the association between slopes and the risks of death and cardiovascular events. RESULTS: Slopes of eGFR had a bell-shaped distribution (mean [SD], −1.5 [−2] ml/min per 1.73 m(2) per year). Declines of eGFR that were steeper than the average decline associated with progressively increasing risks of death (hazard ratio [HR], 1.23; 95% confidence interval [95% CI], 1.09 to 1.39; for a slope 1 SD below the average) and cardiovascular events (HR, 1.19; 95% CI, 1.03 to 1.38). Rises of eGFR or declines lower than the average decline were not associated with the risk of death or cardiovascular events. CONCLUSIONS: In a cohort of individuals with moderate to severe CKD, we observed steep declines of eGFR were associated with progressively increasing risks of death and cardiovascular events; however, we found no increased risks associated with eGFR improvement. These findings support the potential value of eGFR slopes in clinical assessment of adults with CKD.